Factors affecting employee retention at Big Tree Outdoor Sdn Bhd / Ainil Hawa Safiah Mohd Esa - Mohd Esa, Ainil Hawa Safiah (2018)
The concern part of this study is Career Development Opportunity (CDO), Compensation (C) and Manager's Style (MS). As we know that there are numbers of talented employees in every company that Human Resource must care and plan a strategy on how to make the talented employees keeps contribute for the company.